An MPP corrugated cable conduit with anti-electromagnetic shielding and a preparation method thereof
By using metal/hollow glass microbead composite particles and interface coupling agent in MPP corrugated cable conduits, the problem of processing difficulty and impact resistance reduction caused by the increase of fillers and electromagnetic shielding agents is solved, and the high ring stiffness and excellentness of the conduit are achieved. Balance of electromagnetic shielding performance.
Patent Information
- Application Number
- CN202411019524.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-29
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-07-29
AI Technical Summary
When the existing MPP corrugated cable conduits improve electromagnetic shielding performance, they often increase the amount of fillers and electromagnetic shielding agent, resulting in increased extrusion processing difficulty and reduced impact resistance, affecting the overall performance of the conduit.
Using metal/hollow glass microbead composite particles as filler, a metal organic frame (MOF) is formed on the surface of hollow glass microbeads, combined with acrylic elastomer and maleic anhydride graft polypropylene, reduce the amount of electromagnetic shielding agent and improve the catheter Ring stiffness and electromagnetic shielding performance, and the interface performance of the filler and resin substrate are improved through interface coupling agent to ensure the impact resistance of the conduit.
While increasing the stiffness of the catheter ring, the amount of electromagnetic shielding agent is reduced, the extrusion processing performance is improved, the impact resistance and electromagnetic shielding effect of the catheter are guaranteed, and the rigidity and toughness of the catheter are balanced.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of MPP corrugated cable conduits, and in particular to an MPP corrugated cable conduit with anti-electromagnetic shielding and a preparation method thereof. Background Art
[0002] MPP (modified polypropylene) corrugated cable conduit is a cable protection tube with excellent compression resistance, impact resistance and excellent ring stiffness. It can effectively resist the erosion of external pressure and environmental factors and ensure the stable operation of the cable system. This type of conduit is made of modified polypropylene as the main raw material through extrusion molding process. Its inner wall is smooth and convenient for cable threading, which reduces friction damage to the cable and ensures the long-term service life of the cable. In addition, the unique corrugated design not only enhances the ring stiffness of the conduit, but also facilitates the backfilling of fine sand during construction, improving construction efficiency.
[0003] With the continuous development of power engineering, the requirements for cable protection tubes are also increasing. In addition to mechanical properties such as ring stiffness, electromagnetic shielding performance has become an important issue that needs to be urgently improved in cable conduits. In order to improve the ring stiffness and electromagnetic shielding performance of MPP corrugated cable conduits, current technical solutions tend to increase the amount of fillers and electromagnetic shielding agents at the same time. This improves the aforementioned performance of the conduit to a certain extent, but it also brings about the problem of increased difficulty in extrusion processing. In addition, the use of a large amount of fillers may also affect the self-weight and impact resistance of the conduit, reducing its overall performance. Summary of the invention
[0004] The present application provides an MPP corrugated cable conduit with electromagnetic shielding resistance and a preparation method thereof, which can alleviate the influence of the addition of fillers and electromagnetic shielding agents on the mechanical properties of the cable conduit.
[0005] In a first aspect, the present application provides an MPP corrugated cable conduit with anti-electromagnetic shielding, wherein the raw materials of the conduit include, by weight:
[0006] 70-100 parts of polypropylene resin, 5-15 parts of propylene-based elastomer, 5-15 parts of maleic anhydride grafted polypropylene, 5-25 parts of electromagnetic shielding agent, 10-30 parts of filler, and 1-5 parts of interface coupling agent;
[0007] The filler is metal / hollow glass microsphere composite particles, and the preparation method is as follows:
[0008] Dispersing hollow glass microspheres and amino-containing silane oligomers in a solvent to prepare a dispersed solution;
[0009] Add zinc salt and trivalent metal salt to the dispersion solution, stir and disperse, add organic ligand, coordinate the organic ligand with metal ions on the surface of hollow glass microspheres to obtain metal organic framework, separate and filter to obtain intermediate particles; wherein the trivalent metal salt compound is selected from at least one of aluminum salt, gallium salt and indium salt;
[0010] The intermediate particles are dried, pyrolyzed at 450-600°C, and cooled to obtain the product.
[0011] Preferably, the organic ligand is selected from at least one of dimethylimidazole, terephthalic acid and phthalic acid.
[0012] Preferably, the average particle size of the hollow glass microspheres is 10 to 100 microns.
[0013] Preferably, the pyrolysis time is 3 to 5 hours.
[0014] Preferably, the preparation method of the amino-containing silane oligomer is as follows:
[0015] Add aminosilane coupling agent to alcohol solvent, stir evenly to obtain premixed solution, and heat to 40-50°C; drop alcohol-water mixture into the premixed solution, and keep warm for 0.5-1h; then heat to 80-100°C, react for 2-3h, remove alcohol solvent and alcohol obtained by hydrolysis by vacuum distillation, and obtain by filtration.
[0016] Preferably, a phenylsilane coupling agent is further added to the premixed liquid, and the molar ratio of the aminosilane coupling agent to the phenylsilane coupling agent is 1:0.03-0.12.
[0017] Preferably, the phenylsilane coupling agent is selected from phenyltrimethoxysilane and / or phenyltriethoxysilane.
[0018] Preferably, the aminosilane coupling agent is selected from one or more of aminopropyltrimethoxysilane, aminopropyltriethoxysilane, aminopropylmethyldimethoxysilane, aminopropylmethyldiethoxysilane, N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane and N-β-(aminoethyl)-γ-aminopropylmethyldiethoxysilane.
[0019] Preferably, the mass ratio of the hollow glass microspheres to the zinc salt in the dispersed solution is 100:8-15, and the molar ratio of the zinc salt to the trivalent metal salt is 100:1.5-3.5.
[0020] Preferably, the mass ratio of the hollow glass microspheres to the amino-containing silane oligomer is 100:2-6.
[0021] This application uses propylene-based elastomer (POE) as a toughening agent to ensure the impact resistance of the catheter; maleic anhydride grafted polypropylene is used as a compatibilizer to ensure the dispersion between the phases; metal / hollow glass microsphere composite particles are used as fillers to enhance toughness and improve the toughness and ring stiffness of the catheter. The filler has both the characteristics of hollow glass microspheres and a certain electromagnetic shielding effectiveness. It can reduce the amount of electromagnetic shielding agent while enhancing the strength and ring stiffness of the catheter, which helps to alleviate the impact of large amounts of inorganic fillers on the performance of the catheter.
[0022] Specifically, hollow glass microspheres as fillers can achieve the reinforcement and lightweight of the catheter, while improving the fluidity of the resin melt and improving the processing performance. More importantly, the present application forms a metal organic framework (MOF) on the surface of the hollow glass microspheres, and obtains metal-doped zinc oxide with a high free electron content and carrier concentration through calcination, so that it can replace part of the electromagnetic shielding agent and effectively improve the anti-ultraviolet aging performance of the catheter. It should be noted that zinc oxide itself does not have electromagnetic shielding effectiveness. The present application forms an n-type semiconductor by doping aluminum, gallium, indium, etc., to give it this effectiveness.
[0023] In addition, since the deposition of metal ions and organic ligands on the surface of hollow glass microspheres is not uniform, it is not conducive to improving its electromagnetic shielding effect. The present application pre-loads amino-containing silane oligomers on the surface of hollow glass microspheres to form coordination sites with metal ions, and then coordinates with organic ligands to obtain uniformly deposited and dense metal organic frames, thereby obtaining metal / hollow glass microsphere composite particles with better electromagnetic shielding performance.
[0024] Furthermore, in the preparation process of silane oligomers, adding an appropriate amount of phenyl silane coupling agent can generate MOF deposition vacancies on the surface of hollow glass microspheres, thereby obtaining an electromagnetic shielding layer with a certain roughness after calcination, which is beneficial to increase the contact area between the filler and the polypropylene resin and to improve the ring stiffness of the catheter. In order to ensure the performance of the electromagnetic shielding layer, the amount of phenyl silane coupling agent should be controlled within the above reasonable range.
[0025] Preferably, the interfacial coupling agent comprises a first coupling agent and a second coupling agent in a mass ratio of 1:0.2-0.3, wherein the first coupling agent is a silane coupling agent, and the second coupling agent is prepared by free radical copolymerization of a hydroxyl-containing acrylic monomer, methoxy polyethylene glycol methacrylate, and vinyl imidazole in a mass ratio of 10-30:20-40:15-30.
[0026] Preferably, the silane coupling agent is selected from vinyltrimethoxysilane and / or vinyltriethoxysilane.
[0027] Preferably, the hydroxyl-containing acrylic monomer is selected from at least one of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, hydroxybutyl acrylate and N-hydroxymethyl acrylamide.
[0028] The interface coupling agent of the present application can improve the interface performance of fillers, electromagnetic shielding agents and resin substrates. Among them, the two ends of the first coupling agent (silane coupling agent) can form chemical bonds with the resin and filler respectively, and can be cross-linked through their silanol groups to form an enhanced network structure, which is beneficial to improve the rigidity and ring stiffness of the catheter. It should be noted that the coupling interface with excessive rigidity is prone to brittle cracking, and it is difficult to conduct and disperse stress to the filler, which plays a role in alleviating the tip stress and is not conducive to improving the impact resistance of the catheter. To overcome this problem, the present application uses an appropriate amount of the second coupling agent, which can react with the carboxylic acid group in the resin through the hydroxyl group, and coordinate with the metal ions on the surface of the filler and electromagnetic shielding agent through the nitrogen atom in the imidazole to achieve good coupling. And it is not easy to form a coupling interface with excessive rigidity, which is beneficial to the dispersion of stress, thereby improving the impact strength of the catheter.
[0029] In addition, the methoxy polyethylene glycol methacrylate used as the raw material of the second coupling agent can increase the length of its molecular chain, enhance the steric hindrance, and promote the dispersion of the filler.
[0030] Preferably, the free radical copolymerization is carried out in the presence of an initiator, and the amount of the initiator used is 1 to 2% of the total mass of the hydroxyl-containing acrylic monomer, methoxy polyethylene glycol methacrylate, and vinyl imidazole.
[0031] Preferably, the initiator is dibenzoyl peroxide.
[0032] Preferably, the electromagnetic shielding agent is selected from one or more of graphite, carbon fiber, carbon black, carbon nanotubes, and metal powder.
[0033] In a second aspect, the present application provides a method for preparing an MPP corrugated cable conduit with anti-electromagnetic shielding, which comprises:
[0034] According to the raw material ratio of any of the above-mentioned catheters, the electromagnetic shielding agent, filler, and interface coupling agent are stirred evenly in a solvent and dried; then polypropylene resin, propylene-based elastomer, and maleic anhydride grafted polypropylene are added, stirred evenly, and dried to obtain a mixture, and the mixture is extruded on a corrugated pipe extrusion production line to obtain a product at an extrusion temperature of 190 to 220°C.
[0035] Preferably, the solvent is ethanol.
[0036] In summary, this application has the following beneficial effects:
[0037] The present application, by coating the surface of the hollow glass microspheres as reinforcing fillers with a doped metal oxide layer having an electromagnetic shielding effect, can play the role of an electromagnetic shielding agent while achieving the premise of improving the ring stiffness of the cable conduit, thereby reducing the amount of electromagnetic shielding agent used, which is beneficial to improving the difficulty of conduit extrusion processing and ensuring the impact resistance of the conduit. In addition, by using two different interface coupling agents, it is ensured that the coupling interface between the filler and the resin substrate has a relatively moderate rigidity and toughness, so as to ensure the balance between the ring stiffness and impact resistance of the conduit. DETAILED DESCRIPTION
[0038] Preparation Example
[0039] Preparation Example 1-1, an amino-containing silane oligomer, is prepared according to the following operation:
[0040] 1 kg of aminopropyltriethoxysilane was added to 0.3 kg of ethanol, stirred evenly to obtain a premixed solution, and heated to 50°C; 0.12 kg of ethanol and 0.05 kg of water were added dropwise to the premixed solution under stirring to obtain an alcohol-water mixed solution, and the addition was completed within 0.5 h, and the solution was kept warm for hydrolysis reaction for 0.5 h; then the temperature was raised to 90°C, and a condensation reaction was carried out for 2 h. The alcohol solvent and the alcohol obtained by hydrolysis were removed by reduced pressure distillation to obtain an amino-containing silane oligomer.
[0041] Preparation Example 1-2, an amino-containing silane oligomer, is prepared according to the following operation:
[0042] 1 kg of aminopropyltriethoxysilane and 0.06 kg of phenyltriethoxysilane were added to 0.3 kg of ethanol, stirred evenly to obtain a premixed solution, and heated to 50°C; 0.12 kg of ethanol and 0.05 kg of water were added dropwise to the premixed solution under stirring to obtain an alcohol-water mixed solution, the addition was completed within 0.5 h, and the temperature was kept for hydrolysis reaction for 0.5 h; then the temperature was raised to 90°C, and a condensation reaction was carried out for 2 h. The alcohol solvent and the alcohol obtained by hydrolysis were removed by reduced pressure distillation to obtain an amino-containing silane oligomer.
[0043] Preparation Example 1-3, an amino-containing silane oligomer, is prepared according to the following operation:
[0044] 1 kg of aminopropyltriethoxysilane and 0.12 kg of phenyltriethoxysilane were added to 0.4 kg of ethanol, stirred evenly to obtain a premixed solution, and heated to 50°C; 0.15 kg of ethanol and 0.06 kg of water were added dropwise to the premixed solution under stirring to obtain an alcohol-water mixed solution, the addition was completed within 0.5 h, and the temperature was kept for hydrolysis reaction for 0.5 h; then the temperature was raised to 100°C, and a condensation reaction was carried out for 3 h. The alcohol solvent and the alcohol obtained by hydrolysis were removed by reduced pressure distillation to obtain an amino-containing silane oligomer.
[0045] Preparation Example 2-1, a metal / hollow glass microsphere composite particle, the preparation method is as follows:
[0046] 1000 g of hollow glass microspheres (average particle size 30 μm) and 42 g of the amino-containing silane oligomer obtained in Preparation Example 1 were dispersed in 7.5 L of water and stirred for 10 min to obtain a dispersed solution.
[0047] Add 136 g (1 mol) of zinc chloride and 2.7 g (0.02 mol) of aluminum chloride to the dispersed solution, stir and react for 2 h, add 99.6 g (0.6 mol) of terephthalic acid, stir and react for 1 h, so that terephthalic acid and metal ions are coordinated on the surface of hollow glass microspheres to obtain a metal organic framework (MOF), and separate and filter to obtain intermediate particles.
[0048] The intermediate particles were dried at 60°C for 2 h, transferred to a calcining furnace, pyrolyzed at 510°C for 4 h, and then cooled to obtain the product.
[0049] Preparation Example 2-2, a metal / hollow glass microsphere composite particle, the preparation method is as follows:
[0050] 1000 g of hollow glass microspheres (average particle size 30 μm) and 25 g of the amino-containing silane oligomer obtained in Preparation Example 1 were dispersed in 7.5 L of water and stirred for 10 min to obtain a dispersed solution.
[0051] Add 95.2 g (0.7 mol) of zinc chloride and 3.3 g (0.025 mol) of aluminum chloride to the dispersed solution, stir and react for 2 h, add 166 g (1 mol) of terephthalic acid, stir and react for 1 h, so that terephthalic acid and metal ions are coordinated on the surface of hollow glass microspheres to obtain a metal organic framework (MOF), and separate and filter to obtain intermediate particles.
[0052] The intermediate particles were dried at 50°C for 3 h, transferred to a calcining furnace, pyrolyzed at 600°C for 3 h, and then cooled to obtain the product.
[0053] Preparation Example 2-3, a metal / hollow glass microsphere composite particle, the preparation method is as follows:
[0054] 1000 g of hollow glass microspheres (average particle size 30 μm) and 55 g of the amino-containing silane oligomer obtained in Preparation Example 1 were dispersed in 7.5 L of water and stirred for 10 min to obtain a dispersed solution.
[0055] Add 150 g (1.1 mol) of zinc chloride and 4 g (0.03 mol) of aluminum chloride to the dispersed solution, stir and react for 2 h, add 166 g (1 mol) of terephthalic acid, stir and react for 1 h, so that terephthalic acid and metal ions are coordinated on the surface of hollow glass microspheres to obtain a metal organic framework (MOF), and separate and filter to obtain intermediate particles.
[0056] The intermediate particles were dried at 60°C for 3 h, transferred to a calcining furnace, pyrolyzed at 460°C for 4 h, and then cooled to obtain the product.
[0057] Preparation Example 2-4, a metal / hollow glass microsphere composite particle, is different from Preparation Example 2-1 in that the amino-containing silane oligomer obtained in Preparation Example 1-1 is replaced by an equal amount of the amino-containing silane oligomer obtained in Preparation Example 1-2.
[0058] Preparation Example 2-5, a metal / hollow glass microsphere composite particle, is different from Preparation Example 2-1 in that the amino-containing silane oligomer obtained in Preparation Example 1-1 is replaced by an equal amount of the amino-containing silane oligomer obtained in Preparation Example 1-3.
[0059] Preparation Example 2-6, a metal / hollow glass microsphere composite particle, is different from Preparation Example 2-1 in that aluminum chloride is replaced by an equal amount of zinc chloride.
[0060] Preparation Example 2-7, a metal / hollow glass microsphere composite particle, is different from Preparation Example 2-1 in that an equal amount of aminopropyltriethoxysilane is used to replace the amino-containing silane oligomer obtained in Preparation Example 1-1.
[0061] Preparation Example 3-1, an interfacial coupling agent, the preparation steps are as follows:
[0062] Measure 6L of isopropanol in a beaker, weigh 200g of hydroxyethyl acrylate, 330g of methoxy polyethylene glycol methacrylate, and 250g of vinyl imidazole, add them to the beaker, stir and dissolve, add them to the reaction vessel, and fill the reaction flask with nitrogen for 20 minutes to expel the oxygen in the reaction vessel. Weigh 16g of dibenzoyl peroxide and dissolve it in acetone to obtain an initiator solution. When the temperature rises to 60°C, add the initiator solution dropwise through a microinjection pump, and control the dropwise addition time to 1h. After the initiator is added, keep the reaction at 82°C for 5h. After the reaction is completed, cool to room temperature and add 20wt% sodium hydroxide solution to the reaction system, so that the pH value of the reaction system is 7.5-8.0, and discharge the material. The solvent is distilled off under reduced pressure to obtain the product, the product is washed with ether, and dried at 50°C to constant weight.
[0063] Preparation Example 3-2, an interfacial coupling agent, the preparation steps are as follows:
[0064] Measure 6L of isopropanol in a beaker, weigh 130g of hydroxyethyl acrylate, 200g of methoxy polyethylene glycol methacrylate, and 150g of vinyl imidazole, add them to the beaker, stir and dissolve, then add them to the reaction vessel, and fill the reaction flask with nitrogen for 20 minutes to expel the oxygen in the reaction vessel. Weigh 10g of dibenzoyl peroxide and dissolve it in acetone to obtain an initiator solution. When the temperature rises to 55°C, add the initiator solution dropwise through a microinjection pump, and control the dropwise addition time to 1h. After the initiator is added, keep the reaction at 78°C for 6h. After the reaction is completed, cool to room temperature and add 20wt% of sodium hydroxide solution to the reaction system, so that the pH value of the reaction system is 7.5-8.0, and then discharge the material. The solvent is distilled off under reduced pressure to obtain the product, the product is washed with ether, and dried at 50°C to constant weight.
[0065] Preparation Example 3-3, an interfacial coupling agent, the preparation steps are as follows:
[0066] Measure 6L of isopropanol in a beaker, weigh 280g of hydroxyethyl methacrylate, 360g of methoxypolyethylene glycol methacrylate, and 300g of vinyl imidazole, add them to the beaker, stir and dissolve, add them to the reaction vessel, and fill the reaction flask with nitrogen for 20 minutes to expel the oxygen in the reaction vessel. Weigh 15g of dibenzoyl peroxide and dissolve it in acetone to obtain an initiator solution. When the temperature rises to 55°C, add the initiator solution dropwise through a microinjection pump, and control the dropwise addition time to 1h. After the initiator is added, keep the reaction at 80°C for 8h. After the reaction is completed, cool to room temperature and add 20wt% of sodium hydroxide solution to the reaction system, so that the pH value of the reaction system is 7.5-8.0. The solvent is distilled off under reduced pressure to obtain the product, the product is washed with ether, and dried at 50°C to constant weight.
[0067] Preparation Example 3-4, an interfacial coupling agent, differs from Preparation Example 3-1 in that vinyl imidazole is replaced by an equal amount of hydroxyethyl acrylate.
[0068] Preparation Example 3-5, an interfacial coupling agent, differs from Preparation Example 3-1 in that hydroxyethyl acrylate is replaced by an equal amount of vinylimidazole.
[0069] Preparation Example 3-6, an interfacial coupling agent, differs from Preparation Example 3-1 in that methoxy polyethylene glycol methacrylate is replaced by an equal amount of hydroxyethyl acrylate. Example
[0070] The raw materials selected in the embodiment are: propylene-based elastomer (Exxon POE6102), maleic anhydride grafted polypropylene (Arkema CA100), and polypropylene resin (Formosa Plastics PP1005).
[0071] Example 1, an MPP corrugated cable conduit with anti-electromagnetic shielding, the preparation method is as follows:
[0072] Weigh 180g of carbon black (average particle size 5 microns), 200g of metal / hollow glass microsphere composite particles of Preparation Example 2-1, 25g of vinyl trimethoxysilane, and 5g of the interface coupling agent of Preparation Example 3-1, add them into water with a pH value of 4, mix them evenly, filter them, wash them with water until they are neutral, and dry them to obtain a premix. Mix the premix with 850g of polypropylene resin, 100g of propylene-based elastomer, and 120g of maleic anhydride grafted polypropylene, stir them evenly, dry them at 90°C for 2h to obtain a mixture, extrude the mixture on a corrugated pipe extrusion production line to obtain an MPP corrugated cable conduit with an inner diameter of 150mm. The extrusion temperature is 190-220°C.
[0073] Example 2, an MPP corrugated cable conduit with anti-electromagnetic shielding, the preparation method is as follows:
[0074] Weigh 80g of electromagnetic shielding graphite (average particle size 10 microns), 300g of metal / hollow glass microsphere composite particles of Preparation Example 2-2, 15g of vinyl trimethoxysilane, and 4g of the interface coupling agent of Preparation Example 3-2, add them into water with a pH value of 4, mix them evenly, filter them, wash them with water until they are neutral, and dry them to obtain a premix. Mix the premix with 750g of polypropylene resin, 80g of propylene-based elastomer, and 150g of maleic anhydride grafted polypropylene, stir them evenly, dry them at 90°C for 2h to obtain a mixture, extrude the mixture on a corrugated pipe extrusion production line to obtain an MPP corrugated cable conduit with an inner diameter of 150mm. The extrusion temperature is 190-220°C.
[0075] Example 3, an MPP corrugated cable conduit with anti-electromagnetic shielding, the preparation method is as follows:
[0076] Weigh 250g of carbon black (average particle size 5 microns), 150g of the metal / hollow glass microsphere composite particles of Preparation Example 2-3, 30g of vinyl trimethoxysilane, and 9g of the interface coupling agent of Preparation Example 3-3, add them into water with a pH value of 5, mix them evenly, filter them, wash them with water until they are neutral, and dry them to obtain a premix. The premix is mixed with 750g of polypropylene resin, 80g of propylene-based elastomer, and 150g of maleic anhydride grafted polypropylene, stirred evenly, and dried at 90°C for 2h to obtain a mixture, which is extruded on a corrugated pipe extrusion production line to obtain an MPP corrugated cable conduit with an inner diameter of 150mm. The extrusion temperature is 190-220°C.
[0077] Example 4, an MPP corrugated cable conduit with anti-electromagnetic shielding, is different from Example 1 in that the metal / hollow glass microsphere composite particles of Preparation Example 2-1 are replaced by an equal amount of metal / hollow glass microsphere composite particles of Preparation Example 2-4.
[0078] Example 5, an MPP corrugated cable conduit with anti-electromagnetic shielding, differs from Example 1 in that the metal / hollow glass microsphere composite particles of Preparation Example 2-1 are replaced by an equal amount of the metal / hollow glass microsphere composite particles of Preparation Example 2-5.
[0079] Example 6, an MPP corrugated cable conduit with anti-electromagnetic shielding, is different from Example 1 in that the interface coupling agent of Preparation Example 3-4 is used in equal amount to replace the interface coupling agent of 3-1.
[0080] Example 7, an MPP corrugated cable conduit with anti-electromagnetic shielding, is different from Example 1 in that the interface coupling agent of Preparation Example 3-5 is used in an equal amount to replace the interface coupling agent of 3-1.
[0081] Example 8, an MPP corrugated cable conduit with anti-electromagnetic shielding, is different from Example 1 in that the interface coupling agent of Preparation Example 3-6 is used in equal amount to replace the interface coupling agent of 3-1.
[0082] Example 9, an MPP corrugated cable conduit with anti-electromagnetic shielding, differs from Example 1 in that the interface coupling agent in 3-1 is replaced by an equal amount of vinyltrimethoxysilane.
[0083] Example 10, an MPP corrugated cable conduit with anti-electromagnetic shielding, is different from Example 1 in that vinyltrimethoxysilane is replaced by an equal amount of the interface coupling agent of Preparation Example 3-1. Comparative Example
[0084] Comparative Example 1 is an MPP corrugated cable conduit with anti-electromagnetic shielding, which differs from Example 1 in that the metal / hollow glass microsphere composite particles of Preparation Example 2-1 are replaced by an equal amount of hollow glass microspheres.
[0085] Comparative Example 2 is an MPP corrugated cable conduit with anti-electromagnetic shielding, which differs from Example 1 in that the metal / hollow glass microsphere composite particles of Preparation Example 2-1 are replaced by an equal amount of metal / hollow glass microsphere composite particles of Preparation Example 2-6.
[0086] Comparative Example 3, an MPP corrugated cable conduit with anti-electromagnetic shielding, differs from Example 1 in that the metal / hollow glass microsphere composite particles of Preparation Example 2-1 are replaced by an equal amount of metal / hollow glass microsphere composite particles of Preparation Example 2-7.
[0087] Performance testing
[0088] Test 1: Ring stiffness test
[0089] Six specimens of (300±20) mm in length were cut from the MPP corrugated cable conduit. According to the provisions of GB / T 9647-2015 "Determination of Ring Stiffness of Thermoplastic Pipes", the ring stiffness (kPa) of the specimens was tested at 23°C and 3% deformation. Each specimen was tested once, and the arithmetic mean of the test results was taken.
[0090] Test 2: Impact strength test
[0091] According to GB / T 1043.1-2008, the simply supported beam notched impact strength of the sample was tested, and the mixed materials in the embodiment and the comparative example were extruded to prepare samples with a size of 80 mm×10 mm×4 mm. The milling depth was 2 mm, and each group of samples consisted of 5 samples, and the test results were taken as the arithmetic mean.
[0092] Test 3: Electromagnetic shielding performance test
[0093] The electromagnetic shielding effectiveness of the samples in the low frequency band (50Hz~20Hz) was tested with reference to GB / T 12190-2006. Each group of samples consisted of 5 samples, and the arithmetic mean of the test results was taken.
[0094] Table 1. Performance test results
[0095]
[0096] Analysis of test results:
[0097] 1. It can be seen from Examples 1 to 10 and Comparative Examples 1 to 2 and Table 1 that by coating the surface of the hollow glass microspheres with metal-doped zinc oxide having electromagnetic shielding capability, the electromagnetic shielding effectiveness of the catheter ring can be greatly improved while increasing its stiffness.
[0098] 2. Combining Example 1 with Examples 4 to 5 and Table 1, it can be seen that in the preparation process of metal-doped zinc oxide, loading the amino-containing silane oligomer containing phenyl groups on the surface of the hollow glass microspheres instead of loading the amino-containing silane oligomer without phenyl groups can improve the ring stiffness and impact strength of the catheter to a certain extent.
[0099] 3. It can be seen from Example 1 and Examples 6 to 10 and Table 1 that the use of a silane coupling agent in combination with an interfacial coupling agent prepared by free radicals from a hydroxyl-containing acrylic monomer, methoxy polyethylene glycol methacrylate, and vinyl imidazole can give the catheter a relatively balanced rigidity and toughness, ensuring that the catheter also has excellent ring stiffness and impact strength.
[0100] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An MPP corrugated cable conduit with anti-electromagnetic shielding, characterized in that: The raw materials of the catheter include, by mass: 70-100 parts of polypropylene resin, 5-15 parts of propylene-based elastomer, 5-15 parts of maleic anhydride grafted polypropylene, 5-25 parts of electromagnetic shielding agent, 10-30 parts of filler, and 1-5 parts of interface coupling agent; The filler is metal / hollow glass microsphere composite particles, and the preparation method is as follows: Dispersing hollow glass microspheres and amino-containing silane oligomers in a solvent to prepare a dispersed solution; Add zinc salt and trivalent metal salt to the dispersion solution, stir and disperse, add organic ligand, coordinate the organic ligand with metal ions on the surface of hollow glass microspheres to obtain metal organic framework, separate and filter to obtain intermediate particles; wherein the trivalent metal salt is aluminum salt, and the organic ligand is selected from at least one of terephthalic acid and phthalic acid; After the intermediate particles are dried, they are pyrolyzed at 450-600°C and cooled to obtain the product; The preparation method of the amino-containing silane oligomer is as follows: Add aminosilane coupling agent to alcohol solvent, stir evenly to obtain premixed solution, and heat to 40-50°C; drop alcohol-water mixture into the premixed solution, and keep warm for 0.5-1h; then heat to 80-100°C, react for 2-3h, remove alcohol solvent and alcohol obtained by hydrolysis by vacuum distillation, and obtain by filtration.
2. The catheter according to claim 1, characterized in that A phenylsilane coupling agent is also added into the premixed liquid, and the molar ratio of the aminosilane coupling agent to the phenylsilane coupling agent is 1:0.03-0.
12.
3. The catheter according to claim 1, characterized in that The mass ratio of the hollow glass microspheres to the zinc salt in the dispersed solution is 100:8-15, and the molar ratio of the zinc salt to the trivalent metal salt is 100:1.5-3.
5.
4. The catheter according to claim 1, characterized in that The mass ratio of the hollow glass microspheres to the amino-containing silane oligomer is 100:2-6.
5. The catheter according to claim 1, characterized in that The interface coupling agent comprises a first coupling agent and a second coupling agent in a mass ratio of 1:0.2-0.3, wherein the first coupling agent is a silane coupling agent, and the second coupling agent is prepared by free radical copolymerization of a hydroxyl-containing acrylic monomer, methoxy polyethylene glycol methacrylate, and vinyl imidazole in a mass ratio of 10-30:20-40:15-30.
6. The catheter according to claim 5, characterized in that The hydroxyl-containing acrylic monomer is selected from at least one of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, hydroxybutyl acrylate and N-hydroxymethyl acrylamide.
7. The catheter according to claim 5, characterized in that The silane coupling agent is vinyl trimethoxy silane and / or vinyl triethoxy silane.
8. The catheter according to claim 1, characterized in that The electromagnetic shielding agent is selected from one or more of graphite, carbon fiber, carbon black, carbon nanotubes and metal powder.
9. A method for preparing an MPP corrugated cable conduit with anti-electromagnetic shielding, characterized in that: include: According to the raw material ratio of the catheter according to any one of claims 1 to 8, the electromagnetic shielding agent, filler and interface coupling agent are stirred evenly in a solvent and dried; then polypropylene resin, propylene-based elastomer and maleic anhydride grafted polypropylene are added, stirred evenly, and dried to obtain a mixture, and the mixture is extruded on a corrugated pipe extrusion production line to obtain a corrugated pipe, and the extrusion temperature is 190 to 220°C.